2023
DOI: 10.1001/jamanetworkopen.2022.55388
|View full text |Cite
|
Sign up to set email alerts
|

Financial Toxicity Among Patients With Breast Cancer Worldwide

Abstract: ImportanceFinancial toxicity (FT) is the negative impact of cost of care on financial well-being. Patients with breast cancer are at risk for incurring high out-of-pocket costs given the long-term need for multidisciplinary care and expensive treatments.ObjectiveTo quantify the FT rate of patients with breast cancer and identify particularly vulnerable patient populations nationally and internationally.Data SourcesA systematic review and meta-analysis were conducted. Four databases—Embase, PubMed, Global Index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 60 publications
2
23
0
Order By: Relevance
“…However, we did not observe a statistically significant association between cancer history and earnings in the short term (<1 year) or long term. Finally, a number of studies have documented the financial toxicity associated with cancer treatment . Our study extends this result by showing that this financial burden may persist for years after cancer diagnosis.…”
Section: Discussionsupporting
confidence: 77%
“…However, we did not observe a statistically significant association between cancer history and earnings in the short term (<1 year) or long term. Finally, a number of studies have documented the financial toxicity associated with cancer treatment . Our study extends this result by showing that this financial burden may persist for years after cancer diagnosis.…”
Section: Discussionsupporting
confidence: 77%
“…In Western countries, a proportion of patients has to stop trastuzumab before 1 year for a variety of reasons (up to 15% of the patients in pivotal trials) or cannot start the treatment for financial reasons. 16 The figure is even more dismal if we look worldwide: according to a recently published survey on essential anticancer drugs aimed to finalize the WHO Essential Medicine List, trastuzumab is available for only 15% of the patients living in low-middle-income countries, while access to the drug would imply catastrophic expenses for 68% of the patients. 17 In conclusion, at a median follow-up of 9 years, 9 weeks of trastuzumab can guarantee 10-year DFS and OS rates of 78% and 88%, respectively, which, statistically, cannot be claimed as noninferior to the 77% DFS and 89% OS of 1-year trastuzumab.…”
Section: Discussionmentioning
confidence: 99%
“…4 Studies have found the incidence of financial toxicity after breast cancer treatment and reconstruction to be as high as 35.3 and 23%, respectively. 2 5…”
mentioning
confidence: 99%
“…
The financial burden of breast cancer treatment and reconstruction has become a significant concern for patients. [1][2][3] Increasing insurance premiums combined with cost sharing in the form of coinsurance and copays can generate high outof-pocket expenditures for patients. This has created a phenomenon known as financial toxicity, defined as the negative impact high out of pocket costs can have on financial well-being, quality of life, and receipt of the highest quality care.
…”
mentioning
confidence: 99%